Learning Flow Integration Using Google Workspace For Education Schema - Unik Hanifah Salsabila; Tajkiatu Zahra; Noer Hanifah Lestari; Linda Kurniawati; Aliftiya Oktinawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
As COVID-19 eased, there was a significant decline in use of Google Workspace for Education. Previously, Google Workspace for Education was a much-needed solution for educational institutions to support the distance learning process. However, after there are no restrictions and teaching and learning activities can be carried out normally in schools with the aim of finding out the integration of learning flows in the use of Google Workspace for Education after the decline of COVID-19. This research is a qualitative field research with a phenomological approach. The data source comes from the PAI school supervisor in Kulon Progo who is an integration practitioner using Google Workspace for Education in schools. Data collection techniques use interviews, observation and documentation. Data analysis techniques, using reduction, data display, and concluding drawing/verification. The results of this research show that the integration of the learning process with Google Workspace for Education, such as: Google Classroom, Google Meet, Google Forms, Google Drive, etc., has been widely carried out in schools